1999
DOI: 10.1002/hep.510290415
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative portal vein embolization: An audit of 84 patients

Abstract: Preoperative portal vein embolization (PVE) was performed in 84 patients before extensive liver resection for various diseases. By the criteria of liver volumetric determination, some patients were candidates for PVE, whereas others were not, even though the same surgical procedure, such as extended right lobectomy (ERL), was scheduled. PVE using gelatin sponge powder induced hypertrophy in the nonembolized lobe (0%-171%; median, 30%) and proportional atrophy in the embolized lobe in 2 weeks without eliciting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
225
2
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 337 publications
(254 citation statements)
references
References 18 publications
15
225
2
7
Order By: Relevance
“…Following PVE, previous reports have shown that the morphological volumes of the embolized and non-embolized liver change dramatically and rapidly [9,25,26], and our present study confirmed similar results [21,27]. PVE is an established strategy for major hepatectomy in patients with impaired liver function, hilar bile duct carcinoma, or hepatocellular carcinoma [3][4][5][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Following PVE, previous reports have shown that the morphological volumes of the embolized and non-embolized liver change dramatically and rapidly [9,25,26], and our present study confirmed similar results [21,27]. PVE is an established strategy for major hepatectomy in patients with impaired liver function, hilar bile duct carcinoma, or hepatocellular carcinoma [3][4][5][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 88%
“…Better regeneration of non-embolized liver after PVE and hepatectomy may prevent post-hepatectomy complications. Predictors of changes in the embolized and non-embolized liver have been reported [9,10]; however, these have not yet been widely clarified. Our previous examination of predictors of liver volume change after PVE found that alkaline phosphatase (ALP) level was negatively correlated with atrophy of the embolized lobe, and that platelet count was positively correlated with hypertrophy of the non-embolized lobe [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies addressing this issue have yielded conflicting results. [9][10][11]22 In the present study, the global incidence of complications (whether minor or major) and the duration of in-hospital stay were not significantly different in patients with the smallest or largest remnant liver volumes. However, a notable trend is recognized when the remnant volume decreases from 51% to 60% to Ͻ30%: the length of ICU stay doubles and hospital stay is nearly 50% longer in the small residual volume group.…”
Section: S22contrasting
confidence: 43%
“…The indications for PVE in patients with normal liver parenchyma vary among reports, although at hepatobiliary surgery centers, patients are typically selected by liver remnant size. Methods of measurement of the future remnant vary, 7 but most investigators propose that preoperative PVE is indicated when the measured future liver remnant volume is expected to be less than 25% to 45% of the preoperative functional liver volume (FLV) [8][9][10][11][12] or when the standardized FLV will be less than 1% of the patient's body weight (BW). 13 Recognition that these criteria have been determined empirically 7 and that the benefits of PVE may not be as obvious for patients with normal underlying liver as for patients with chronic liver disease 14,15 has led to increased interest in better definition of the indications for PVE and clearer determination of the limits of safe resection in patients with normal liver.…”
mentioning
confidence: 99%
“…The negative correlation between FLR% before PVO and degree of hypertrophy, as shown in Fig. 2, has been described previously [24], but we are unaware of previous results connecting tumour size to the degree of hypertrophy (Figs. 3-4).…”
Section: Influence Of Tumour Size On Regenerationsupporting
confidence: 72%